Plant Biochemistry - P.M. Dey; Harborne, J B (New Delhi Academic Press, 2000)
The Plant the Cell and its Molecular Components;Photosynthesis;Carbohydrate Metabolism: Primary Metabolism of Monosaccharides; Carbohydrate Metabolism: Storage Carbohydrate; Carbohydrate Metabolism: Structural Carbohydrate: Plant Lipid Metabolism; Primary Nitrogen Metabolism; Nucleic Acids and Proteins; Regulation of Gene Expression in Plants; Phenolic Metabolism; Isoprenoid Metabolism; Special Nitrogen Metabolism; Biochemical Plant Pathology; Biochemical Plant Ecology; Plant Cell biotechnology.